2008
DOI: 10.1103/physrevlett.100.135003
|View full text |Cite
|
Sign up to set email alerts
|

Generating High-Current Monoenergetic Proton Beams by a CircularlyPolarized Laser Pulse in the Phase-StableAcceleration Regime

Abstract: A new ion acceleration method, namely, phase-stable acceleration, using circularly-polarized laser pulses is proposed. When the initial target density n(0) and thickness D satisfy a(L) approximately (n(0)/n(c))D/lambda(L) and D>l(s) with a(L), lambda(L), l(s), and n(c) the normalized laser amplitude, the laser wavelength in vacuum, the plasma skin depth, and the critical density of the incident laser pulse, respectively, a quasiequilibrium for the electrons is established by the light pressure and the space ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
186
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 394 publications
(194 citation statements)
references
References 25 publications
7
186
0
1
Order By: Relevance
“…The RPA scheme is supposed to have the potential to produce even GeV proton beams [30][31][32][33][34][35][36][37][38][39][40][41][42]. Often ultrathin target of tens or hundreds of nanometers along with circularly polarized laser pulses are adopted in order to produce quasimonoenergetic proton beams, even though a linearly polarized laser pulse may also work out in some parameter range [43].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The RPA scheme is supposed to have the potential to produce even GeV proton beams [30][31][32][33][34][35][36][37][38][39][40][41][42]. Often ultrathin target of tens or hundreds of nanometers along with circularly polarized laser pulses are adopted in order to produce quasimonoenergetic proton beams, even though a linearly polarized laser pulse may also work out in some parameter range [43].…”
Section: Introductionmentioning
confidence: 99%
“…Thus the hole-boring stage is almost skipped and the plasma sheath layer is immediately pushed away from its original position. Afterwards, it is steadily accelerated as a whole for a long time [31]. Qiao et al proposed the ''relativistic hole-boring'' regime [38], which requires that the laser intensity to be as high as to satisfy I L % 0:25m i n i c 3 so that the hole-boring velocity approaches the speed of light, realizing smooth connection between the short hole-boring stage and light sail stage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Existing studies have shown that proton beams at the GeV level can be obtained by radiation pressure acceleration (RPA) using > 10 22 W/cm 2 lasers. [7][8][9][10][11][12] In that scheme the light pressure in the plasma is balanced by the charge-separation field, so that the electron and proton layers co-move as a double-layer. [13][14][15][16][17][18][19][20] However, because of instability the acceleration length is limited to less than hundreds of micrometers and it is difficult to increase the ion energy.…”
Section: Introductionmentioning
confidence: 99%
“…Further, these energetic ion beams have potential applications in fast ignition for inertial confinement fusion, 4 medical therapy, 5 proton imaging, 6 and so on. MeV−GeV protons may be obtained through different mechanisms, 7 such as target normal sheath acceleration (TNSA), [8][9][10][11][12][13][14] radiation pressure acceleration (RPA), [15][16][17][18][19][20][21][22] collision-less shock acceleration, [23][24][25][26][27] breakout afterburner (BOA) laser acceleration, 28 and so on. Of these mechanisms, TNSA may be the most feasible for experimental application.…”
mentioning
confidence: 99%